Edukasi Dan Pengembangan Pengetahuan Siswa Siswi Smp Makassar Tentang Tiga Ancaman Dasar Kesehatan Reproduksi Remaja (Triad) - Mukriani, Mukriani; Yermi, Yermi; Utari, Utari; Ula, Zumrotul; Hamzah, Ricda Nurhikmayanti; Bahrun, Suriani; Lonik, Lorensius (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Basic efforts to overcome these problems require correct and comprehensive knowledge about reproductive health in order to achieve good reproductive health. The purpose of this community service activity is to increase students' knowledge about the Three Basic Threats to Adolescent Reproductive Health. The method used in the Community Service activity is education and development of knowledge of Makassar junior high school students about the three basic threats to adolescent reproductive health (TRIAD). The results of community service are an increase in students' knowledge about the three basic threats to adolescent reproductive health. The conclusion of this activity is the formation of a group of teenagers who can be used as Agents of Change or agents of renewal.